Words at work and play three decades in family and community life - Heath, Shirley Brice (Cambridge, UK Cambridge University Press, 2012)
"Childhood and family life have changed significantly in recent decades. What is the nature of these changes? How have they affected the use of time, space, work and play? In what ways have they influenced face-to-face talk and the uses of technology within families and communities? Eminent anthropologist Shirley Brice Heath sets out to find answers to these and similar questions, tracking the lives of 300 black and white working-class families as they reshaped their lives in new locations, occupations and interpersonal alignments over a period of thirty years. From the 1981 recession through the economic instabilities and technological developments of the opening decade of the twenty-first century, Shirley Brice Heath shows how families constantly rearrange their patterns of work, language, play and learning in response to economic pressures. This outstanding study is a must-read for anyone interested in family life, language development and social change"-Publisher.
"In transcribing the speech of the characters in this book, I have made no effort to provide phonetic representation. Words are presented in an approximation to standard orthography, with as much "eye-dialect" as seems necessary to indicate the varieties of English used, primarily African American English Vernacular and Piedmont Carolina dialect. The children of the two communities grew up learning local dialect forms. Trackton children who did not leave the community until they were in their adolescence retained more features of African American English Vernacular than those who left before they entered school"-Publisher.
1. On being long in company -- 2. A boy finds his mama(s) -- 3. The closeness of strangers -- 4. Embracing talk -- 5. Lines of vision -- 6. The hand of play -- 7. Ways with time and words -- 8. Shaping the mainstream.
Includes bibliographical references (pages 208-215) and index.
Keywords: Language and culture -- Piedmont (U.S. : Region); Sociolinguistics -- Piedmont (U.S. : Region); English language -- Dialects -- Piedmont (U.S. : Region); African American children -- Piedmont (U.S. : Region) -- Language